Parenting Adolescents in an Increasingly Diverse World: Defining, Refining, and Extending Theory and Research. (18th August 2018) - Hussong, Andrea M.; Jones, Deborah J.
Abstract : This introduction to the Special Issue on Parenting Adolescents in an Increasingly Diverse World explores how increasing population diversity may provide a context for changes in the parenting of adolescents. In this issue, authors (1) explore the context for asking questions about parenting adolescents and diversity, (2) consider parents, adolescents, and parenting in different diversity contexts, and (3) reflect on crosscutting themes. Two articles examine the parenting in an international context and within changing domestic demographics. Four articles focus on parenting adolescents in traditionally marginalized groups with the goal of identifying lessons for supporting all youth in navigating an increasingly diverse world. Finally, two articles synthesize these articles to suggest important directions for future research.